Obtenção de micro e nanocelulose a partir de biomassa lignocelulósica de resíduo da casca do ingá-cipó (Inga edulis Mart.) via tratamento químico - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
The search for new sustainable materials causes a gradual increase in studies aimed at the use of renewable raw materials, seeking to generate products that are not aggressive to the environment, maintaining their quality and performance. The fruits of the ingá-vine (Inga edulis Mart.) family (Fabaceae), generate residues that are great sources of lignocellulosic biomass, a material that is the largest source of renewable carbon in the world, this material is mainly composed of three polymers: cellulose, hemicellulose and lignin. The pre-sent work aimed to obtain crystalline micro and nanocellulose from lignocellulosic biomass from the peel of the ingá-cipó fruit via chemical treatment, as well as to carry out its physicochemical and morphological characterization. The peels were subjected to a sequential extraction of hemicellulose and lignin, followed by the synthesis of micro and nanocellulose by acid hydrolysis. The material obtained was characterization through infrared with Fourier transform (FTIR) for the observation of the functional groups present and transmission electron microscopy (TEM) with the objective of observing the morphology. Through FTIR analysis, it was possible to verify the presence of typical cellulosic functional groups. The images from the TEM, helped the visualization of the crystalline micro and nanocellulose, where it is possible to observe elon-gated and thin beams, organized side by side.
Obtaining micro and nanocellulose from biomass lignocellulosic analysis of ingá-cipó bark residue (Inga edulis Mart.) via chemical treatments
Keywords: Energia - Fontes alternativas; Biomassa vegetal - Amazônia; Inga - Produtos; Celulose; CIENCIAS EXATAS E DA TERRA; Inga edulis Mart.; Celulose; Caracterização; Hidrólise ácida